Assessing the service quality in Software-as-a-Service from the customers’ perspective: a methodological approach and case of use - Freitas,André Luís Policani (2017)
Abstract Despite the advances in the evaluation of the quality of Software-as-a-Service (SaaS), new studies seem to be necessary, since the existing criticisms concerning the SERVQUAL scale and the lack of studies concerning the use of SERVPERF for this purpose. This work aims to fulfil this gap by proposing a methodological approach to assess the SaaS service quality by measuring SaaS customers’ satisfaction. Factor analysis is used to summarize the information contained in the original items into a smaller set of new dimensions and Quartile analysis is suggested to determine the most critical items. By conducting a study, the factors that most influence customer’s satisfaction are customer service, customer assistance and the reliability of SaaS. Most of the critical items are associated with the transparency and accuracy in correcting errors, the company's interest in solving customer problems, SaaS application's ability to meet business requirements, implemented updates and regularity of service performance.